2003
DOI: 10.1029/2002je001896
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for the formation of benzene in the atmosphere of Titan

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are important interstellar species, and their precursor benzene (C6H6) has been detected in our solar system. In this study the possibility of benzene formation in the atmosphere of Titan is investigated. Benzene abundance in Titan's atmosphere is found to be rather highly dependent on the assumed mechanism for benzene production. Assuming reactions involved in this mechanism to proceed at the rate corresponding to 300 K, a value of 5.4 × 10−7 at 2 × 10−5 mbar is found f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
173
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(179 citation statements)
references
References 42 publications
6
173
0
Order By: Relevance
“…1. Eddy diffusion profiles from various photochemical models (Yung et al 1984;Strobel et al 1992;Toublanc et al 1995;Lara et al 1996;Wilson & Atreya 2004;Vinatier et al 2007;Lavvas et al 2008;Hörst et al 2008;Krasnopolsky 2009). …”
Section: Chemical Schemementioning
confidence: 99%
“…1. Eddy diffusion profiles from various photochemical models (Yung et al 1984;Strobel et al 1992;Toublanc et al 1995;Lara et al 1996;Wilson & Atreya 2004;Vinatier et al 2007;Lavvas et al 2008;Hörst et al 2008;Krasnopolsky 2009). …”
Section: Chemical Schemementioning
confidence: 99%
“…Without this information, the chemical identity of the fragments is unknown, and therefore their further reactivity. This situation has for long prevented the use of a large corpus of experimental BR data in detailed chemistry models, and many modelers have instead implemented a default "H-loss" scheme, where the parent ions looses a single H atom [3][4][5][6][7][8]. The "H-loss" scheme is not supported by the experiments: many ions present major dissociation pathways involving heavy atoms bond breaking, for instance C 4 H + 8 [9] or HC 3 N + and other nitrile ions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the kinetic models of the PAH formation and growth in low temperature environments such as on Titan or in the interstellar medium relied upon the models of PAH and soot formation in combustion processes and assumed that similar mechanisms are important both at combustion temperatures (1000 -2500 K) and in the extraterrestrial, low temperature environments (10 -150 K). [27][28][29][30] Wilson et al 31 suggested, for instance, that once the first aromatic ring is available, the further growth of PAHs proceeds by the hydrogen-abstraction-acetylene-addition (HACA) mechanism, 30,32 which is believed to be the most important PAH formation mechanism in combustion flames. 27 However, an apparent flaw of these models is that both hydrogen abstraction and acetylene addition reactions exhibit significant barriers and as a result are very slow at low temperatures relevant to the atmospheric conditions on Titan or in the Interstellar Medium (ISM).…”
Section: Figure 1: Depiction Of Various Combustion Intermediate Mole mentioning
confidence: 99%